Mas'alah Inna wa akhwatuha 'inda al Shaykh Ibn 'Aqil wa "uthaimin fi Sharh Alfiyah Ibn 'Aqil : Dirasah tahliliyyah muqaranah fi Nahw - Muh. Ilham Shohib (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2019)
etik,1./ws.c.1